Desenvolvimento de programa computacional para determinação de valores de concentração de tensões - Silva, Dirceu Jesus Lima da (2016)
The present work consists in the development of a procedure for determining theoretical values of stress concentrators, from previously established equations in the literature, in order to awaken in the engineering student, more interest and greater involvement with a matter as important as the subject matter, as well as providing the designer, even if a beginner, to obtain those values through a user-friendly interface of a computer program, in a simple and objective way, which will be made available for free use via the web. This study is justified by the need for designers to determine the concentration factors quickly to optimize the design time in the design of mechanical elements, while also offering the user possible alternatives aimed at minimizing the negative effects caused by the stress concentrators. The graphical interface, easy to use in determining the concentration values of stresses for discontinuities previously inserted in its database, also allows the user to insert in the same, new discontinuities and their equations, as well as the edition of already constant values In the database. In order to evaluate the operation of the program, the modeling of three classic situations of stress concentrators was carried out. These situations were compared analytically, numerically by the finite element method and experimentally by means of standardized tests. As a result, the stress concentration factors calculated analytically by the program were compared and validated.